Perceived justice at workplace and organizational commitment - Zhilla, Eralda (Array, 2020)
The aim of this study is to investigate the relationship between the employees’ perception of justice at the workplace, in relation to the organizational commitment. The study was carried out in Kosovo and its findings contribute to the service industry, being the most developed in that region. This especially applies to the banking sector, which is still in a transitional phase in Kosovo, with the potential benefit, in terms of better qualification of the staff. The data is collected from a sample of 256 participants, mainly from the banking sector (N=148), but also other sectors, such as the public sector (N=28), private business (N=34), NGOs (N=26) and others (N=20). This study hypothesizes that the perceived organizational justice has a positive effect on organizational commitment, with the empirical results supporting the hypothesis.